DEVELOPMENT AND TESTING OF A SOLAR ADSORPTION REFRIGERATOR UNDER HAZY CONDITION - Abur, Benjamin Ternenge; Waziri, Abudharr Bello; Duvuna, Gideon Ayuba; Oguche, Emmanuel Enemona; Onyema, Abams; Shammah, Innocent Micah; Julius, Eze Ekene (FUDMA Journal of Sciences, 2025)
Preservation of foods, drinks, fruits, fish, and perishables using cleaner form of energy at lowfinancial cost has necessitated the adoption of solar powered refrigeration system mostespecially in locations with known viable solar resources. A 0.36m 2 solar-powered adsorptionrefrigeration system utilizing an activated carbon/methanol pair was developed, tested, andevaluated under a cloudy sky condition of harmattan haze of Bauchi weather condition inJanuary. A single 4mm plane glass forms the collector employing the location latitude as theinclination angle. Copper tubes arranged in parallel and connected to two headers areembedded underneath the absorber and, then coated with black paint. Collector air tightnessis improved by the use of glazing rubber. Five liters of water in the cooling cabinet attained13°C after 56 hours of experiment achieving a 41% temperature reduction and, 0.56 coolingcoefficient of performance. This work indicates the practicability of solar adsorptionrefrigeration in the tropics amidst cloudy sky conditions. For improved performance underunfavorable weather conditions, provision should be made for auxiliary heating. Theapplications of this form of refrigeration will curb the use of conventional energy, minimizegrid dependence, reduce household recurrent bills, and ozone layer-depletingchlorofluorocarbons (CFCs).
Keywords: Activated carbon/methanol; Adsorption; Cooling; Development; Solar energy